Passive IoT-based positioning technology development status and evolutionary trends - QIAN Hongyu; LI Yuan; WANG Qing; WANG Yamin; XIAO Shanpeng (Dianxin kexue)
Passive IoT-based positioning systems are low-cost and taggable, making them suitable for scenarios that require the positioning of a large number of targets. Traditional passive IoT positioning is mostly applied to indoor scenarios such as asset management, material tracking. With the emergence of cellular passive IoT, passive IoT positioning technology will have a broader range of applications. On the basis of analyzing the principles and characteristics of different positioning technologies, the latest research progress of passive IoT positioning was introduced, and the passive IoT positioning technologies were summarized into three categories: geometrical measurement-based positioning methods, fingerprint feature-based positioning methods, and imaging technology-based positioning methods, according to their implementation principles. In view of the fact that most of the current research adopted the data obtained under the traditional passive IoT architecture and protocol for localization, the future development direction of passive IoT positioning technology was analyzed from three dimensions: architectures, protocols and data. The aim is to provide new ideas for researching passive IoT positioning technology.